2021
DOI: 10.7759/cureus.12722
|View full text |Cite
|
Sign up to set email alerts
|

Late Complications After Previous Surgical Repair for Coarctation With Extra-Anatomic Bypass Graft: Report on Two Cases

Abstract: Surgical correction of aortic coarctation (CoA) has been the standard treatment in infants and adolescents to prevent late consequences related to obstruction and distal hypoperfusion. Several surgical techniques for CoA repair have traditionally been applied. However, late complications, including re-CoA and pseudoaneurysm formation, are not uncommon. The incidence of complications is highly related to the type of initial surgery. Here, we are reporting two cases of late complications related to an infrequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The appropriate surgical technique for COA repair often remains unclear for adult patients 10 . Surgical techniques to treat COA include resection with end-to-end anastomosis, prosthetic patch aortoplasty, subclavian flap aortoplasty, interposition grafting and extra-anatomic bypass grafting 2 , 4 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate surgical technique for COA repair often remains unclear for adult patients 10 . Surgical techniques to treat COA include resection with end-to-end anastomosis, prosthetic patch aortoplasty, subclavian flap aortoplasty, interposition grafting and extra-anatomic bypass grafting 2 , 4 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Extra-anatomical bypass grafting has been recommended for complex COA cases (COA coexists with the other valvular, vascular and ventricular diseases) 4 , 5 , 10 , 12 15 as well as isolated COA cases (COA does not coexist with the other cardiovascular pathologies) 11 , 12 in adults. Furthermore, surgical treatment for COA carries some risk for spinal cord injury, occurring in approximately 0.5% of patients being operated on for coarctation 16 , studies have shown that extra-anatomic bypass minimizes the risk of paraplegia 2 , 15 .…”
Section: Introductionmentioning
confidence: 99%